Declining utilization of urodynamic studies in urological care in Germany: time to say goodbye? - Baunacke, Martin; Kontschak, Livia; Menzel, Viktoria; Grabbert, Markus; Borkowetz, Angelika; Mehralivand, Sherif; Eisenmenger, Nicole; Huber, Johannes; Thomas, Christian; Schultz-Lampel, Daniela (World journal of urology, 2024)
Introduction The number of urodynamic studies (UDS) has been declining steadily in recent decades, yet the reasons behind this trend remain poorly understood. This study aims to investigate the structural aspects of UDS in urology and explore the factors contributing to this decline. Material & methods We surveyed all urological departments performing UDS as well as a representative sample of private practices in Germany in 2023. We examined structural situation, waiting times, capacities and limitations of UDS. All invasive urodynamic examinations were defined as UDS. Results In 2019, 259/474 (55%) urological departments in Germany performed UDS. 206/259 (80%) urological departments responded to the survey. 163/200 (82%) urological departments stated that their capacities were exhausted, a main reason being lack of medical and nursing staff. 54.8% urological departments performed more than 50% of their UDS for referring physicians. Urological departments with a low number of UDS/year (≤ 100) showed a shorter waiting time (up to 4 weeks: 49% vs. 30%; p = 0.01), reduced UDS capacities (55% vs. 12%; p < 0.001) and these capacities were often not fully utilized (25% vs. 9%; p = 0.007). 122/280 (44%) office urologists responded to the survey. 18/122 (15%) office urologists performed UDS. Main reasons for not offering UDS were lack of personnel and low reimbursement. Conclusion In German urological departments, UDS capacities are consistently fully utilized, primarily due to staffing shortages. This trend towards centralization prompts questions about the role of UDS in urologists’ training.